YOUTH AND MORALITY IN KENYA: THE ROLE OF SCIENCE AND RELIGION - Erixon, Wamalwa Martin (IJRDO - Journal of Applied Management Science, 2016)
Morality is said to be beliefs or ideas about what is right and wrong and about how people shout behave. It refers to a system of beliefs and values concerning how people should behave, which is accepted by a particular person or a group. In short, it be seen as a standard of behaviour. Since it has to do with right and wrong, it is evident that any group of people or society would desire to follow or do what is morally right and avoid what is morally wrong. In this context, every society would strive to inculcate and nurture what it upholds as morally good to its members. The youth are an important section of this membership as it is in them that the future of any society and its morality abound. It thus follows that the morality of the youths should be emphasized for a moral society tomorrow. Nonetheless, it is claimed that today there are tangible and visible changes in the realm of morals among the young people. There is an outcry about the deterioration of moral values among the youth in Kenya. This poses a great challenge as regards the future. Therefore, there is an urgency to address this situation in order to rebuild the moral standard of our youth, hence the nation of tomorrow. This paper analyzes the role of religion and science in addressing the problem of youth and morality in Kenya. The basic assumption in this paper is that both science and religion are unique realities in our life, and that each can contribute uniquely in combating societal problems, hence bringing about an upright society. The paper further asserts that neither science nor religion can solely address such societal problems without involving the other; they are complimentary realities, hence the need for dialogue. The ideas advanced in this paper will be significant and an addition to the already established approaches to the problem of youth and morality in Kenya. The paper also poses a challenge to the conflicting relationship between science and religion, hence re-thinking the approach towards one another.